Pentingnya Pendidikan Agama Islam dalam Menghadapi Tantangan Globalisasi - Muhajir Musa; Agus Faisal Asyha; Trisna Rukhmana; Al Ikhlas; Muqarramah Sulaiman Kurdi; Mursyidi A Jalil (Journal on Education, 2024)
This research discusses the central role of Islamic Religious Education in responding to and overcoming complex challenges arising from globalization. Through a qualitative approach and case studies, this research explores the understanding and implementation of Islamic values ​​amidst continuously developing global dynamics. The research results show that Islamic Religious Education has a crucial role in shaping individual Islamic character and perspective. By integrating local values ​​into a global context, religious education is able to provide a strong moral foundation to face the challenges of globalization. Teachers are identified as the main pillar in conveying religious values, acting as facilitators and effective role models. By aligning Islamic values ​​with the global context, religious education creates a bridge that connects Islamic traditions with current developments. The implications of this research include recommendations for improving the curriculum, increasing teacher training, and developing learning strategies that are responsive to the dynamics of global change. The conclusion of this research provides an in-depth view of how important Islamic religious education is in forming a generation that is strong and moral in facing the complex challenges of the era of globalization.